Assessing the Financial and Environmental Sustainability in Raw Rubber Processing; a Case Study with Ribbed Smoked Sheet Manufacture in Sri Lanka - Pasan Dunuwila; V.H.L. Rodrigo; Naohiro Goto (Indonesian Journal of Life Cycle Assessment and Sustainability, 2018)
Sri Lanka has been renowned for its top quality natural rubber products. Among the locally manufactured raw rubber types, ribbed smoked sheets (RSS) hold a significant position as it entails ca. 50% of total natural rubber production in island. With no sufficient information on effectiveness in the use of materials and finance and then environmental impacts of RSS manufacture, this study aimed at assessing RSS manufacturing process adopting Material flow analysis, Material flow cost accounting and environmental Life cycle assessment in three factories in view of providing effective suggestions for making the system to be more cost efficient and environmentally friendly. Results indicated that manufacture cost, financial loss and GHG emissions generated by processing 1 MT of RSS were LKR 104,004 ± 6,336, LKR 1,007 ± 44 and 38.0 ± 2.1 kg CO2e, respectively (mean ± standard error). As an improvement option, installing single-day smoke dryers was proposed. This option could reduce firewood consumption per 1 MT of RSS by ca. 30% resulting in 0.1% and 14% of reductions in manufacture cost and GHG emissions, respectively. Implications of these findings are also discussed.